تقييم النشاط الاشعاعي الطبيعي لعينات تربة من مناطق مختلفة في محافظة بغداد - عبد الوهاب رضا, Ali; رسول سالم, Sanaa; فاضل طالب, Dunia (مجلة كلية التربية, 2020)
In this paper, the measurement of natural radioactivity in various areas of Baghdad governorate using NaI(Tl) system, twenty soil samples were collected (ten from the surface and ten form 20cm depth). Analysis of gamma spectrum for each sample and calculations of specific activity appears to show that the average concentrations of U-238, Th-232 and K-40 were (55.30, 49.18, 545.24) Bq/kg respectively, which was more than the worldwide average. While the average values of Radium equivalent, absorbed dose, annual effective dose, internal and external hazard index for each sample were found to be (160.82 Bq/kg, 67.48 nGy/h, 0.08 mSv/y, 0.39, 0.50) respectively, all of these values were lower than the permissibility limit except the absorbed dose value which higher than the global limit (55nGy/h).